Peningkatan Kompetensi Siswa SMKN 1 Madiun Melalui Pelatihan Arduino Untuk Aplikasi Otomasi - R. Gaguk Pratama Yudha; Apriyanto, R. Akbar; Echsony, Mohammad Erik Echsony; Adiratna Ciptaningrum; Andhika Putra Widyadharma; R. Oktav Yama Hendra; M. Iqbal Raysha Widodo (LPPM UMRI, 2026)
This Community Service Program aimed to improve the competence of students at SMKN 1 Madiun in Arduino microcontroller applications through project-based training for simple automation systems. The program adopted a Participatory Action Research approach consisting of needs assessment, theoretical instruction, Arduino programming practice, project development, and evaluation. The training covered Arduino fundamentals, programming, sensor and actuator integration, and the implementation of simple automation applications. Participant performance was evaluated using pre-tests, post-tests, practical assessments, and satisfaction questionnaires. The results showed that the average score increased from 38.4% in the pre-test to 87.2% in the post-test, representing a 48.8% improvement. The average practical assessment score reached 87.8, while 90% of participants successfully completed the assigned automation projects. Participant satisfaction reached 95.6%, indicating an excellent response to the training. These findings demonstrate that Project-Based Learning effectively improves students' knowledge, technical skills, and practical competence in Arduino-based automation. Furthermore, the program strengthens collaboration between higher education institutions and vocational schools to support industry-oriented technical education.